Does the human capital discourse promote or hinder the right to education? The case of girls, orphans and vulnerable children in Rwanda - Balsera, Maria Ron (Journal of International Development, 2011)
This paper studies the implications of considering education as a human right and examining it through the lens of the human capital discourse. It uses Polanyi's idea of decommodification, as discussed by Offe and Esping-Andersen, as well as Foucault's concept of governmentality, to analyse the changes that are taking place in the education sector in post-genocide Rwanda. It focuses on the consequences of the human capital discourse for girls, orphans, children with disabilities and Batwa in Rwanda. The paper concludes that although the human capital discourse has brought attention and resources to education, the situation has worsened for some marginalised groups leading to growing inequalities and discrimination. Copyright © 2011 John Wiley & Sons, Ltd.
Keywords: Rwanda; commodification; decommodification; human capital; neoliberal governmentality; right to education